La erosión por arroyada en una estación experimental (Requena, Valencia) - Neus La-Roca Cervigon (Cuadernos de Investigación Geográfica, 2013)
This paper is an attempt to establish the erosion rate on three slopes with different exposure and vegetal cover by means of the Gerlach trap method, in an area of Mediterranean dry climate. Detailled complementary analysis of slope morphology and soil and sediments texture allow us to make conclusions about the process dynamic. At the end small criticism of the Gerlach method accuracy to our Mediterranean ambient is pointed out.